Polyamine biosynthetic pathways and their relation with the cold tolerance of maize (Zea mays L.) seedlings. (1st November 2020) - Gao, Canhong; Sheteiwy, Mohamed S.; Han, Jiajun; Dong, Zhaorong; Pan, Ronghui; Guan, Yajing; Alhaj Hamoud, Yousef; Hu, Jin
ABSTRACT: Background: The present study was designed to investigate the inhibition role of two polyamine biosynthesis inhibitors, i.e., D-arginine (D-Arg) and DL-α-difluoromethylornithine (DFMO), in polyamine biosynthesis under chilling stress in different tissues of two maize inbred lines – Huang C (chilling-tolerance) and Mo17 (chilling-sensitive). Results: The results showed that exposure to the lower concentration of polyamine biosynthesis inhibitors improved seedlings growth, such as the root length, root and shoot fresh weight, chlorophyll a (chl a). The effectiveness of 10 µM D-Arg treatments was more prominent than those of 10 µM DFMO. However, the higher concentration of inhibitors suppressed seedlings growth, and the exposure to 100 µM DFMO caused stronger decreases in the photosynthetic pigments, such as chlorophyll a (chl a), chlorophyll b (chl b), total chlorophyll and carotenoids, than the other treatments. Meanwhile, the inhibitor treatments caused the lower content of putrescine (Put) in roots, mesocotyls and coleoptiles in both maize inbred lines as compared with untreated plants. However, the lower concentration (10 µM) of polyamine biosynthetic inhibitors improved the Spd content, except 10 µM D-Arg in root of Huang C, and 10 µM DFMO in coleoptiles of both Mo17 and Huang C. The correlation analysis found that Spd was positively significantly correlated with root length and shoot fresh weight of seedling. Conclusion: It was showed that the Spd played an important role in seedling growth improvement. At the same concentration of polyamine biosynthetic inhibitors, the Put contents in different tissues of the seedlings treated with DFMO were generally lower than those treated with D-Arg, except for Put contents in root of Mo17 with 10 µM treatment. Moreover, the treatments of 100 µM were more prominent than those of 10 µM treatments. Exposure to 100 µM D-Arg and 100 µM DFMO could each decrease the activities of Arginine decarboxylase (ADC), Ornithine decarboxylase (ODC) and S-adenosylmethionine decarboxylase (SAMDC) in all maize tissues. However, the decrease of the ADC activity was more prominent in 100 µM D-Arg-treated seedlings, while the decrease of SAMDC and ODC activities was prominent in 100 µM DFMO-treated seedlings. Genes involved in polyamine biosynthesis, such as ADC, ODC, SAMDC, and PAO, showed different expression patterns in response to chilling stress and polyamine biosynthesis inhibitors. This study suggested that Put was synthesized via both the ADC and ODC pathways after chilling stress, with the ODC pathway being the major one.